Un approfondimento relativo alla velocità istantanea di reazione (Chimica nella Scuola, 2023)
Usually, at the level of basic chemistry in the first two years of secondary school, the reaction rate is defined by referring to the average speed; sometimes and only briefly the concept of instantaneous speed is mentioned. In this article a possible in-depth analysis of the instantaneous reaction rate is provided; the analysis is not based on a theoretical-descriptive way, but uses an experimental-inductive approach.
Keywords: velocità di reazione; velocità istantanea; velocità media; coefficiente angolare di una retta